Analysis of Competitive Activity and Characteristics of Applied Loads of Highly Skilled Taekwondo Players (Eurasian Journal of Research, Development and Innovation, 2022)
In order to resolve the issues mentioned, it was necessary to single out the main factors in the preparatory structure of highly qualified Taekwondo players, as well as determine the factors that can be changed in the process of training, the most important of which is the training process.